2022
DOI: 10.11613/bm.2022.010708
|View full text |Cite
|
Sign up to set email alerts
|

Verification of automatic analysers Roller 20PN and iSED for measuring erythrocyte sedimentation rate

Abstract: Automated erythrocyte sedimentation rate (ESR) analysers are based on different methodology than Westergren method. It is questionable whether ESR values obtained from those analysers are comparable with determined values with Westergren method. The aim was verification of the precision, method comparison and accuracy of automated ESR analysers: Roller 20PN (Alifax S.p.A., Polverara, Italy) and iSED (Alcor Scientific, Smithfield, USA). Blood samples (N = 752 for Roller 20PN and N = 213 for iSED) were sampled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, consistent with previous findings [13,18], sam- ples with low ESR levels correlated better than high ESR levels samples, as can be seen in Figure 1, probably due to the nondilution with sodium citrate of the samples, as in the Westergren test. The high levels of ESR results obtained by MINI-CUBE, through the mathematical calculation of the optical distance of the red blood cell aggregation and the top of the plasma, indicated a slight difference with the high levels of ESR results obtained from the gold standard [11,19,20]; anyhow, despite the larger bias, the lower correlation for high ESR values do not influence the clinical evaluation. It was observed that the ESR high levels were predominantly from samples from cancer patients, due to the inflammatory status generated by the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 94%
“…However, consistent with previous findings [13,18], sam- ples with low ESR levels correlated better than high ESR levels samples, as can be seen in Figure 1, probably due to the nondilution with sodium citrate of the samples, as in the Westergren test. The high levels of ESR results obtained by MINI-CUBE, through the mathematical calculation of the optical distance of the red blood cell aggregation and the top of the plasma, indicated a slight difference with the high levels of ESR results obtained from the gold standard [11,19,20]; anyhow, despite the larger bias, the lower correlation for high ESR values do not influence the clinical evaluation. It was observed that the ESR high levels were predominantly from samples from cancer patients, due to the inflammatory status generated by the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 94%
“…The guidelines for the definition and determination of reference intervals indicate that partitioning should be considered when there are significant differences among subgroups defined by age, sex, and common exposures [ 5 , 21 ]. The ESR increases with age in adults, and at a given age is higher in females than in males [ 5 , 11 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the ICSH group published new recommendations, stressing the importance of ensuring that measurements obtained in different laboratories were comparable [ 7 ]. ICSH and CLSI therefore made new recommendations in 2010 and 2011 [ 23 , 26 ]. The ICSH document recognized that automated methods were routinely used in many laboratories, using diluted or undiluted samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations